(untitled) (Journal of Engineering, 2008)
The present work studied the drop size distribution in the RTL contactor using two liquid-liquid systems, xylene-acetone-water and kerosene-acetone-water. Process variables studied were: rpm (10-50 min-1), continuous phase flow rate (4-12 l/h), dispersed phase flow rate (4-12 l/h), and concentration (0.1-0.5 mole/l). It was found that Sauter mean drop diameter (d32) decreased with increasing rpm and continuous phase flow rate, and decreasing dispersed phase flow rate and concentration. An empirical correlation, with a correlation coefficient equal to (92.6%), relating d32 with process variables was developed having the form: